1990
DOI: 10.1099/0022-1317-71-6-1275
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization epitopes of human rhinovirus type 2

Abstract: Fourteen neutralizing monoclonal antibodies recognizing human rhinovirus (HRV) type 2 have been used to select a total of 51 virus escape mutants. Crossresistance analysis of the mutants, together with RNA sequencing and identification of amino acid substitutions, have revealed three neutralization sites on the virus surface. Two of these appear to correspond to the NIm-IA and NIm-II sites described for HRV-type 14, although there are also substantial differences. The third site has not been described previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…This group raised approximately 250 MAbs to peptides representing an antigenic site on poliovirus type 3, but found that the vast majority were peptide-specific, and the two that bound to virus did not recognize immobilized peptide. Conversely, all of the anti-viral MAbs raised to HRV2 by Appleyard et al (1990) were specific for virus particles (S. Russell, personal communication) as they were directed against conformational determinants. The only anti-HRV2 antibody that also bound peptide was the 8F5 MAb described by Skern et al (1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group raised approximately 250 MAbs to peptides representing an antigenic site on poliovirus type 3, but found that the vast majority were peptide-specific, and the two that bound to virus did not recognize immobilized peptide. Conversely, all of the anti-viral MAbs raised to HRV2 by Appleyard et al (1990) were specific for virus particles (S. Russell, personal communication) as they were directed against conformational determinants. The only anti-HRV2 antibody that also bound peptide was the 8F5 MAb described by Skern et al (1987).…”
Section: Discussionmentioning
confidence: 99%
“…HRV2 was obtained from the MRC Common Cold Research Unit, Salisbury, U.K., grown in HeLa (OH5) cells and plaque-purified as previously reported (Appleyard et al, 1990). Virus used for neutralization assays was stored as clarified tissue culture harvest in an equal volume of glycerol at -20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These data define four neutralizing immunogenic sites (NIm-Ia, Ib, 11, and 111) for HRV14 (Sherry et al, 1986), and three (designated A, B, and C) for HRV2 (Appleyard et al, 1990). Site A and B correspond to NIm-IA and NIm-11; however, whereas in HRV14 VP2 contributes most of the amino acid residues to NIm-11, in HRV2 VP1 is primarily involved in the architecture of site B.…”
mentioning
confidence: 91%
“…These are referred to as NIm Ia, NIm Ib, NIm II and NIm III, according to the viral protein on which they are principally located. Sites corresponding to, but significantly different from, NIm Ia and NIm II also appear on human rhinovirus serotype 2 (HRV-2) (Appleyard et al, 1990). Synthetic peptides representing linear portions of the protein sequence of HRV-2 have previously been shown to be recognized by antisera raised against HRV-2 (Francis et al, 1987a).…”
mentioning
confidence: 99%